RETRACTED: Exploring the potential of black fungus, Auricularia auricula, as a feed additive in African catfish, Clarias gariepinus, farming - Wei, Lee Seong; Adrian Susin, Alvin Amos; Tahiluddin, Albaris B.; Kien, Liew Vui; Wee, Wendy (Elsevier BV, 2024)
This study explores the beneficial effects of Auricularia auricula (AA) as a feed additive in promoting growth, digestive enzyme activities, antioxidative responses, heat tolerance, and disease resistance against Edwardsiella tarda in African catfish (Clarias gariepinus) farming. The application of feed additives is a hot topic in recent aquaculture studies aimed at promoting the growth and health of aquaculture species. After 8 weeks of feeding trial, the results of the present study revealed that fish-fed AA diets performed significantly better (p < 0.05) compared to the control group in growth performances, including final weight, weight gain, and specific growth rate. The highest performances were observed in the fish-fed AA at 3 and 4 %. A similar trend was also observed in the values of feed conversion ratio, hepatosomatic index, and visceral somatic index, with the lowest values (p < 0.05) in the fish-fed AA at 3 and 4 %. AA diets enhanced the activities of all tested digestive enzymes (amylase, protease, and lipase) significantly (p < 0.05), with the highest activities in the fish-fed AA at 3 and 4 %. Meanwhile, fish-fed AA diets exhibited significantly higher (p < 0.05) catalase, superoxide dismutase, and glutathione peroxidase activities both before and after heat stress, with the highest activities in the fish that received AA at 3 and 4 %. Furthermore, AA diets stimulated disease resistance in African catfish, with the fish-fed AA at 4 % performing the highest cumulative survival rate (73.3 ± 5.77 %) post-infection with E. tarda in African catfish. The findings of the current study suggest that AA has huge potential as a feed additive in African catfish farming.
Keywords: Research Article